2021
DOI: 10.3390/ijms22105320
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiles of Maternal and Neonatal Endothelial Progenitor Cells in Preeclampsia

Abstract: Preeclampsia is associated with an increased cardiovascular morbidity of mother and offspring, thus contributing to a substantial burden in women and children’s health. It has been proven that endothelial progenitor cell (EPC) numbers and functional characteristics are impaired in cardiovascular disease and preeclampsia, although causative factors for the latter have remained elusive. MicroRNA (miRNA) modifications are a potential mechanism through which exposure to an altered environment translates into the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…We deliberately focused on fetal cord blood ECFC because they reflect fetal endothelial function and play an essential role in endothelial health, repair, and vasculogenesis making them an important tool for pharmaceutical intervention for offspring from preeclamptic pregnancies. Moreover, in our own studies, we have shown that ECFC maintain a stable miRNA profile up to passage 5 28 and remain their functional (normal ECFC) and dysfunctional (preeclamptic ECFC) characteristic ex vivo 13,14,47,48 and could therefore provide some insight into the long‐term cellular effects in the offspring. The results of this study shed light on the mechanisms mediating endothelial dysfunction after pregnancy and possibly causing the increased incidence of cardiovascular alterations in offspring after maternal preeclampsia.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…We deliberately focused on fetal cord blood ECFC because they reflect fetal endothelial function and play an essential role in endothelial health, repair, and vasculogenesis making them an important tool for pharmaceutical intervention for offspring from preeclamptic pregnancies. Moreover, in our own studies, we have shown that ECFC maintain a stable miRNA profile up to passage 5 28 and remain their functional (normal ECFC) and dysfunctional (preeclamptic ECFC) characteristic ex vivo 13,14,47,48 and could therefore provide some insight into the long‐term cellular effects in the offspring. The results of this study shed light on the mechanisms mediating endothelial dysfunction after pregnancy and possibly causing the increased incidence of cardiovascular alterations in offspring after maternal preeclampsia.…”
Section: Discussionmentioning
confidence: 85%
“…Since ECFCs have similar function in adults, it is conceivable that comparable effects could play a role in mothers after preeclampsia. In our previous study, we show differences in the miRNA profile of maternal and fetal ECFC from preeclamptic compared to healthy pregnancies 28 . However, more extensive investigations on whether the dysregulated miRNAs of maternal ECFC also cause a functional restriction in maternal ECFC are still lacking.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The age of the offspring involved in the studies varied greatly. There were a few different life stages, namely prenatal age (19th-37th week of gestation) (16), neonates (aged less than four weeks old) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), infants (aged 2-12 months old) (21), toddlers (aged 1-3 years old) (27), children (aged 5-12 years old) (27,28) and adolescent (aged 12-19 years old) (27). The study population also varied.…”
Section: Study Characteristicsmentioning
confidence: 99%